2018
DOI: 10.1108/ijes-04-2017-0020
|View full text |Cite
|
Sign up to set email alerts
|

Death in the Spanish fire services: a curriculum development study

Abstract: Purpose The purpose of this paper is to understand the need and resources firefighters have to deal with death and dying (D&D) that they encounter whilst on duty and to present a curriculum to support D&D issues for firefighters. Design/methodology/approach A qualitative methodology involving focus groups was conducted in two fire stations in Spain. The sample was 38 male participants with a mean age of 46 y/o (range: 30-59 years) and an average tenure of employment of 18 years (range: 6-35 years). D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Behavior of team members (Rank 4) is assigned to the superordinate category support between colleagues in the present study and can thus be linked to a lack of support between colleagues [ 11 , 13 ]. Decision-making , which is mentioned frequently in other studies [ 9 , 10 , 12 , 15 , 25 ], is the superordinate category of Decision in case of situation change/ decide between different alternatives 2 (Rank 5). The other aspects of the existing research breach of standards and lack of situational awareness [ 9 , 10 ] are also reflected in the teamwork-related stressors of this study and thus show that the present results can systematically confirm and expand the beginnings that were already researched in the existing literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Behavior of team members (Rank 4) is assigned to the superordinate category support between colleagues in the present study and can thus be linked to a lack of support between colleagues [ 11 , 13 ]. Decision-making , which is mentioned frequently in other studies [ 9 , 10 , 12 , 15 , 25 ], is the superordinate category of Decision in case of situation change/ decide between different alternatives 2 (Rank 5). The other aspects of the existing research breach of standards and lack of situational awareness [ 9 , 10 ] are also reflected in the teamwork-related stressors of this study and thus show that the present results can systematically confirm and expand the beginnings that were already researched in the existing literature.…”
Section: Discussionmentioning
confidence: 99%
“…Various reasons arising from teamwork (decision-making, lack of communication, breach of standards, human error, and lack of situational awareness) together account for 38% of all firefighter injuries during firefighting operations [ 9 ]. Another study identified nine stressors that contribute to firefighter fatalities during operations in Spain, of which two are teamwork and decision-making under stress [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Potentially relevant studies were retrieved in full, and their citation details imported into the JBI System for the Unified Management, Assessment and Review of Information (JBI SUMARI; JBI, Adelaide, Australia). 31 The full text of selected citations was assessed in detail against the inclusion criteria by 2 independent reviewer (MI and KM). Reasons for exclusion of full-text studies that did not meet the inclusion criteria were recorded and reported.…”
Section: Study Selectionmentioning
confidence: 99%